Intracerebellar upregulation of Rheb(S16H) ameliorates motor dysfunction in mice with SCA2 - Kim Sehwan; Park Junwoo; Eo Hyemi; Lee Gi Beom; Park Se Min; Shin Minsang; Lee Seung Eun; Nam Youngpyo; Kim Sang Ryong (Acta Pharmacologica Sinica, 2025)
Cerebellar ataxia (CA) is characterized by impaired balance and coordination due to the loss of cerebellar neurons caused by various factors, and effective treatments are currently lacking. Recently, we observed reduced expression of signaling molecules in the mammalian target of rapamycin complex 1 (mTORC1) pathway in the cerebellum of mice with spinocerebellar ataxia type 2 (SCA2) compared with wild-type mice. To investigate the effects of mTORC1 upregulation on motor dysfunction in mice with SCA2, we administered an intracerebellar injection of adeno-associated virus serotype 1 carrying a constitutively active form of Ras homolog enriched in brain [Rheb(S16H)], which is an upstream activator of mTORC1. This treatment led to increased Rheb(S16H) expression in calbindin-D28K-positive Purkinje cells and increased levels of neurotrophic factors. Additionally, Rheb(S16H) upregulation reduced abnormal behaviors and protected Purkinje cells in mice with SCA2. Our findings suggest that upregulating Rheb(S16H) in the cerebellum may be a promising therapeutic strategy for hereditary CA.